The earthworm fauna of regenerating forests and anthropogenic habitats in the coastal region of Paraná - Roembke, Joerg; Schmidt, Petra; Hofer, Hubert (Pesquisa Agropecuaria Brasileira, 2010)
The aim of this study was to evaluate abundance, biomass and diversity of earthworms in the southern coast region of the Mata AtlÔntica biodiversity hotspot. Aátotal of 51ástudy sites in pastures, banana monocultures, mixed agroforestry systems, secondary forests in succession and old-growth forests near the coast of Paranß, Brazil, were evaluated. Each site was sampled once. Species richness of the earthworms was generally low and varied little between sites. At all sites except for one, the peregrine species Pontoscolex corethrurus (Glossoscolecidae) strongly dominated. Three other peregrine species, Amynthas corticis, Amynthas gracilis (Megascolecidae) and Ocnerodrilus occidentalis (Ocnerodrilidae), were frequent in moist sites. No autochthonous species were found. Abundance and biomass of earthworms varied strongly within and between sites (0–338 individuals m-2, 0–96 g m-² fresh weight). Pastures had significantly lower abundance than all other sites. The forest sites had similar earthworm abundance and biomass, with a tendency to be higher in younger succession stages. The coastal plain region has been strongly altered by human activities. Reasons for the lack of any autochthonous species and the dominance of one peregrine species require further investigation.